An Approximate Solution of Higher Order Ordinary Differential Equations Using Modified Adomian Decomposition Method - Nuha Mohammed Dabwan; Yahya Qaid Hasan (IJRDO -JOURNAL OF MATHEMATICS, 2020)
Modified Adomian Decomposition Method (MADM) is used in thisarticle to solve higher order ordinary differential equations. Someexamples are proposed to show the ability of the methed for solvingthis type of equations.